THE IMPORTANCE OF PSYCHOMOTOR DEVELOPMENT IN SCHOOL EDUCATION, WITH PHYSICAL EDUCATION: A LITERARY REVIEW - Silva, Giuliano Roberto da; Reis, Alexandre Maia; Campos de Oliveira, Juliana Bonaccorsi; Neiva, Cassiano Merussi [UNESP]; Santos, Daniel dos (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
Psychomotricity has the function to emphasize the relation between the motricity, the mind and the affectivity. A child whose Psychomotricity is not well developed may present difficulties in school learning, for example, a child who does not have a definite dominant side may have difficulty in reading, confusion in discerning b from d, difficulty in copying from the vertical plane To the horizontal, among others. That is why we see the importance of working Psychomotrity since the beginning of literacy, and the most indicated form is the playful form. This study aimed to prove the importance of psychomotor development in school education with the help of the Physical Education professional. After the Literary Review, it is concluded that as a science for education, Psychomotricity, aims to educate the movement, while at the same time developing intelligence and affectivity. Therefore, psychomotor education is indispensable to every child. Every school should promote stimuli to develop in its students the skills of body schema, laterality, spatial structuring, temporal orientation, tone, posture and balance, pre-writing and fine psychomotricity.
Keywords: Psychomotricity; Schooling; Physical Education